Empirical comparison of subjective probability elicitation methods* - WRIGHT, WILLIAM F. (Contemporary Accounting Research, 1988)
The direct magnitude and bisection subjective probability elicitation methods are compared based on the environmental (relative frequency) accuracy of the resulting probabilities and the acceptability of the elicitation methods. Each subject utilized, and provided acceptability indications for, both methods. Interactive elicitation software, including histogram‐like graphical displays of the probabilities for both elicitation methods, were provided to aid the subjects and provide for a more refined comparison of the methods. Second‐year graduate business students, knowledgeable about both the task context and subjective probabilities, completed the experiment. Direct elicitation of probabilities provided significantly more accurate subjective probabilities than did the bisection method and the former method also was significantly more acceptable to the subjects.